Electronically tunable quadrature oscillator using current-controlled voltage conveyors - Piyatat, T.; Tangsrirat, W.; Surakampontorn, W. (My University, 2005)
A translinear-based bipolar realization of the current-controlled voltage conveyor (CCVC) is described. An electronically tunable quadrature oscillator is then proposed which uses only three proposed CCVCs and two grounded capacitors for its realization. The proposed oscillator circuit provides two quadrature sinusoidal outputs with 90° phase difference. The oscillation condition and the oscillation frequency are independently controllable by electronic means through adjusting the external dc bias current. PSPICE simulation results that confirm the theoretical are also given and discussed. © 2005 IEEE.